2017
DOI: 10.1016/j.ijpara.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Heritable genetic transformation of Strongyloides stercoralis by microinjection of plasmid DNA constructs into the male germline

Abstract: Heretofore, transgenesis in the parasitic nematode genus Strongyloides has relied on microinjecting transgene constructs into gonadal syncytia of free-living females. We now report transgenesis in Strongyloides stercoralis by microinjecting constructs into the syncytial testes of free-living males. Crosses of individual males microinjected with a construct encoding GFP with cohorts of 12 non-injected females produced a mean of 7.28 ± 2.09 transgenic progeny. Progeny of males and females microinjected with dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Sexual reproduction by S . stercoralis has also been confirmed recently by experimental crossing of free-living male and female worms harboring discrete reporter transgenes[ 65 ]. Although these findings do not exclude that asexual species or strains might exist, even within what is currently referred to as S .…”
Section: Discussionmentioning
confidence: 95%
“…Sexual reproduction by S . stercoralis has also been confirmed recently by experimental crossing of free-living male and female worms harboring discrete reporter transgenes[ 65 ]. Although these findings do not exclude that asexual species or strains might exist, even within what is currently referred to as S .…”
Section: Discussionmentioning
confidence: 95%
“…Further adding to the potential utility of S . stercoralis , a recent study demonstrated that heritable transgenesis is also possible by microinjection of plasmid constructs into the testicular syncytium of free-living males [ 41 ]. Future CRISPR-Cas9 strategies simultaneously targeting both S .…”
Section: Discussionmentioning
confidence: 99%
“…Intragonadal microinjection has also been used to generate transgenics in the closely related nematode Parastrongyloides trichosuri, a parasite of Australian brushtail possums that can cycle through multiple free-living generations (Grant et al, 2006). Strongyloides stercoralis free-living adult males are also amenable to genetic transformation via microinjection into the syncytial testes (Shao et al, 2017). The ability to cycle through one or more free-living generations is specific to the genera Strongyloides and Parastrongyloides (Lok, 2007).…”
Section: Transgenesis In Strongyloides Speciesmentioning
confidence: 99%